2018
DOI: 10.1111/eip.12773
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the prevalence of dissociative disorders and severe dissociative symptoms in first episode psychosis

Abstract: Aim Increasing evidence suggests that childhood trauma and dissociation are associated with psychotic symptoms and disorders. Significant rates of dissociative disorders and clinical levels of dissociative symptoms are found in chronic schizophrenia. To date, no studies have examined the prevalence of these in a first episode psychosis (FEP) group. This study aimed to investigate the prevalence of dissociative disorders and symptoms in a FEP sample as well as the prevalence of severe dissociative symptoms in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…We also demonstrate that the concurrent validity of pathological dissociation is as good as the concurrent validity of depression in patients with SSDs as reported in the literature. Consistent with the literature, the dissociative subgroup was more likely to report high-betrayal traumas (Sun et al, 2019 ; Yu et al, 2010 ). Dissociative patients also reported more psychotic symptoms than nondissociative patients (Longden et al, 2020 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We also demonstrate that the concurrent validity of pathological dissociation is as good as the concurrent validity of depression in patients with SSDs as reported in the literature. Consistent with the literature, the dissociative subgroup was more likely to report high-betrayal traumas (Sun et al, 2019 ; Yu et al, 2010 ). Dissociative patients also reported more psychotic symptoms than nondissociative patients (Longden et al, 2020 ).…”
Section: Discussionsupporting
confidence: 80%
“…Yu et al ( 2010 ) administered clinical interviews together with the DDIS to 96 randomly selected inpatients with clinically diagnosed schizophrenia in Shanghai and reported that the prevalence of a DD was 15.3% and that those with a DD were significantly more likely to report childhood abuse, but none of them had a prior clinical diagnosis of DD in their medical record. In a more recent study, Sun et al ( 2019 ) administered the SCID-D to 66 patients with first episode psychosis and reported that 13.6% of participants met criteria for either a past or current diagnosis of a DD; similar to the Shanghai study, they found that the dissociative subgroup had significantly higher rates of childhood trauma.…”
Section: Introductionmentioning
confidence: 84%
“…Dissociation has a well-established presence in psychosis populations (Ross and Keyes, 2004;Moskowitz, 2011;Vogel et al, 2013;Renard et al, 2017;Sun et al, 2018a), and may have a pivotal role in the formation and maintenance of psychotic symptoms (Schäefer et al, 2012;Sun et al, 2018a;Freeman et al, 2019;Treise et al, 2019;Longden et al, 2020). Dissociative symptoms have been found in both longer-term psychotic illness (Ross and Keyes, 2004) and in first episode of psychosis (Sun et al, 2018b), and are mostly associated with positive symptoms, specifically delusions and hallucinations (Spitzer et al, 1997;Ross and Keyes, 2004;Kilcommons and Morrison, 2005;Lysaker and LaRocco, 2008;Schäefer et al, 2012;Vogel et al, 2013;Schroeder et al, 2016;Sun et al, 2018b;Longden et al, 2020;Varese et al, 2020). Moreover, the severity of dissociative phenomena may fluctuate in step with psychotic symptoms, with higher levels of dissociation in the acute illness phase compared to stabilization (Schäefer et al, 2012).…”
Section: Dissociative Compartmentalization In Difficult-to-treat Psychotic Phenomenamentioning
confidence: 99%
“…Moreover, the severity of dissociative phenomena may fluctuate in step with psychotic symptoms, with higher levels of dissociation in the acute illness phase compared to stabilization (Schäefer et al, 2012). Despite evidence supporting a relationship between dissociative and psychosis phenomena, evidence supporting dissociation as a treatment focus for positive symptoms of psychosis (Longden et al, 2020;Varese et al, 2020), and proposals that some psychotic symptoms may be better conceptualized as forms of dissociation (Moskowitz et al, 2009;Longden et al, 2020), the nature of this connection has remained elusive (Sun et al, 2018b;Freeman et al, 2019;Treise et al, 2019). This uncertainty may have contributed to the fact that treatment guidelines [National Institute of Health and Care Excellence (NICE), 2014] have not yet included dissociative processes as targets for routine psychological treatment in populations with psychosis (Newman-Taylor and Sambrook, 2013; Treise et al, 2019).…”
Section: Dissociative Compartmentalization In Difficult-to-treat Psychotic Phenomenamentioning
confidence: 99%
See 1 more Smart Citation